Diabetes Food Plan 2018
DOI: 10.5772/intechopen.71529
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic and Safety Properties of Ethanolic Leaf Extract of Corchorus olitorius in Alloxan-Induced Diabetic Rats

Abstract: Diabetes is a major metabolic disease of global concern. Ethanolic extract of Corchorus olitorius leaf was investigated for antidiabetic activity in alloxan-induced diabetic rats. A total of thirty-six albino rats (Rattus norvegicus) with body weight 150.50 AE 10.50 g were randomly selected into six groups (A-F). Group A animals were non-diabetic and received 0.5 mL distilled water, groups B, C, D, E and F were made diabetic by administration of alloxan monohydrate (150 mg/kg, body weight i.p). Group B was dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Phytochemical content of seed extract has alkaloids, saponins which shows hypoglycaemic effect, and other great potential treating effects [15]. Some findings suggest the use of Corchorus olitorius as body cooling drink [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical content of seed extract has alkaloids, saponins which shows hypoglycaemic effect, and other great potential treating effects [15]. Some findings suggest the use of Corchorus olitorius as body cooling drink [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…For the induction of diabetes, alloxan monohydrate was used ( Dunn and McLetchie, 1943 ). Freshly prepared alloxan solution (1055.8 µMol/Kg) in saline was given to experimental rats via an intra-peritoneal route ( Olusanya and Ifeoluwa, 2018 ). After 48 h, blood glucose levels of experimental rats were measured by using the tail prick methodology.…”
Section: Methodsmentioning
confidence: 99%
“…Alloxan is a potent inducer of pancreas toxicity and is therefore used for experimental diabetes induction (Brenna et al, 2003). Alloxan induces a multiphasic blood glucose response when injected into an experimental animal, with consistent fluctuations in the plasma insulin level associated with structural damage to beta cells (Olusanya and Ifeoluwa, 2018). The pathology of DM is attenuated by insulin therapy and orally by hypoglycemic medications such as biguanides and sulfonylureas.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ethanolic extract of the C. olitorius leaf significantly ( p < 0.05) elevated levels of serum and liver bilirubin (direct and total), transaminases (AST and ALT), alkaline phosphatase, urea, creatinine, total cholesterol, triglyceride, and LDL-C, as well as reduced levels of total protein, globulin, albumin, and HDL-C in the alloxan-induced untreated diabetic rats normalized upon treatment with the ethanolic extract of C. olitorius leaf. Thus, the ethanolic extract of C. olitorius leaf exhibited antihyperglycemic and anti-dyslipidemic effects, and hence it could be considered safe for use as an antidiabetic recipe [ 122 ]. Another group of researchers pointed out that ethanolic seed extract of C. olitorius is a valuable antidiabetic agent due to its ability to lower blood glucose levels [ 32 ].…”
Section: Biological Activitymentioning
confidence: 99%